2019
DOI: 10.1038/s41598-019-44274-4
|View full text |Cite
|
Sign up to set email alerts
|

Iodine solubility and speciation in glasses

Abstract: The study of iodine in glasses and melts is critical in many areas, from geosciences to materials science to waste management. Glasses in the ternary system Na 2 O-B 2 O 3 -SiO 2 were studied with the goal of identifying a glass matrix able to dissolve large quantities of this element, and to identify the main parameters affecting the solubility of iodine. Two sets of experiments were carried out: the first one with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…We have shown from Figure 4 that T g is influenced by the presence of I and that increasing I decreases the T g . Comparable behavior has been observed in previous work for B‐rich borosilicate glass compositions 7 . We also show that the influence of I on T g is not the same in between the compositions with a decreasing slope that is more important for ISG than for NH.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We have shown from Figure 4 that T g is influenced by the presence of I and that increasing I decreases the T g . Comparable behavior has been observed in previous work for B‐rich borosilicate glass compositions 7 . We also show that the influence of I on T g is not the same in between the compositions with a decreasing slope that is more important for ISG than for NH.…”
Section: Discussionsupporting
confidence: 86%
“…Recent work on B-rich glasses showed that I decreases T g . 7 It appears consistent with the fact that I is considered as a melting accelerator and fining agent. 3,36 However, up to now, investigation of the I effect on T g for borosilicate glass composition relevant to nuclear waste immobilization is not available.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations